Penerapan Algoritma Arithmatic Coding Pada Aplikasi Kamus Teknologi Informasi Berbasis Android - Ariska, Riris (TIN: Terapan Informatika Nusantara, 2021)
The development of technology is getting faster and more widespread. Currently, there are many different types of operating systems (OS) for both computers and handset applications. Dictionaries on cell phones are more practical, because at this time users need a lot of information quickly anywhere and without time limits. File compression is one of the important aspects in the development of information technology. The speed of delivery is very much needed and depends on the size of the information, one of which is by compressing the data. If the compression process runs effectively, the resulting file can be smaller than the original file. The effectiveness of the data compression system depends on the modeling and coding used. Based on the problem above, the researcher made a title, namely "Application of the Arithmetic Coding Algorithm in Android-Based Technology Dictionary Applications". Which is expected with this research can help companies in determining more systematic decisions.